Redefining Citizenship in Motion: Smart Governance and the Digital Transformation of Non-Permanent Residence Letters in Indonesia - Fua, Maria Dewi Ayuyanti Bire; Wirantari, I Dewa Ayu Putri (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Digital transformation in public services is reshaping the concept of citizenship through smart governance approaches, particularly in managing population documents such as the Non-Permanent Residence Certificate (Surat Keterangan Tinggal Tidak Tetap/SKTT). This study analyzes the service innovations implemented by the Civil Registry Office (Disdukcapil) of Badung Regency in issuing SKTTs as a response to the needs of non-permanent residents, including seasonal workers, university students, and temporary migrants. Using a qualitative method involving in-depth interviews, participatory observation, and document analysis, the study reveals several key innovations: integration with the Badung Smart civil registration system (SIAK), mobile service delivery, synchronization with Village Information Systems (SID), and simplified bureaucratic procedures. These efforts have significantly improved service efficiency, reduced processing time, increased application volume, and enhanced citizen satisfaction. The findings highlight a shift in the meaning of citizenship—from a static administrative status to one defined by digital access and service responsiveness. This study contributes a novel perspective by linking population administration innovation with the evolving concept of citizenship in the context of mobility and digitalization. To ensure sustainability, the article recommends strengthening human resource capacity, expanding public outreach, and transforming bureaucratic culture toward citizen-oriented service delivery.